Stephen W. Hawking, A Brief History of Time. From the Big Bang to Black Holes. Introduction by Carl Sagan. New Edition. Bantam Books. New York-Toronto-London-Sydney- Auckland 1990. VIII + 198 páginas. ISBN 0-553-34614-8 - Sacchi, Mario Enrique (1994)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina